2016
DOI: 10.1177/1368430216678329
|View full text |Cite
|
Sign up to set email alerts
|

Identity uncertainty and UK–Scottish relations: Different dynamics depending on relative identity centrality

Abstract: Drawing on uncertainty-identity theory, we investigated how people respond differently to identity uncertainty at a superordinate (i.e., UK) or subgroup (i.e., Scottish) level depending on the subjective self-conceptual centrality of subgroup relative to superordinate group; altering superordinate and subgroup identification and attitude toward subgroup relations to the superordinate group in the context of Scotland's bid for independence from the UK (N = 115). Hierarchical regression analyses confirmed our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…When people are uncertain about themselves, they identify with groups, especially highly entitative groups (Grant & Hogg, 2012;Sherman, Hogg, & Maitner, 2009) and disidentify from low entitative groups or uncertainty-inducing groups (Hogg, Adelman, & Blagg, 2010;Hogg, Meehan, & Farquharson, 2010;Hogg et al, 2007). Directly relevant to the present research, two correlational studies (Jung et al, 2016(Jung et al, , 2018 found a puzzling asymmetry in the relationship between identity-uncertainty and recategorization in the context of hierarchial identities. When people are uncertain about a subgroup which is central to their self-concept, they recategorize and identify more strongly with a superordinate group; however, uncertainty about a superordinate group was not associated with subgroup identification.…”
Section: Self-categorization Depersonalization and Uncertainty Rementioning
confidence: 58%
See 2 more Smart Citations
“…When people are uncertain about themselves, they identify with groups, especially highly entitative groups (Grant & Hogg, 2012;Sherman, Hogg, & Maitner, 2009) and disidentify from low entitative groups or uncertainty-inducing groups (Hogg, Adelman, & Blagg, 2010;Hogg, Meehan, & Farquharson, 2010;Hogg et al, 2007). Directly relevant to the present research, two correlational studies (Jung et al, 2016(Jung et al, , 2018 found a puzzling asymmetry in the relationship between identity-uncertainty and recategorization in the context of hierarchial identities. When people are uncertain about a subgroup which is central to their self-concept, they recategorize and identify more strongly with a superordinate group; however, uncertainty about a superordinate group was not associated with subgroup identification.…”
Section: Self-categorization Depersonalization and Uncertainty Rementioning
confidence: 58%
“…The extent to which participants felt uncertain about their superordinate identity was measured with five items adapted from Jung et al (). Participants indicated how well each of five statements described their feelings about ethnic Korean identity at that time: “I am uncertain about who we the ethnic Korean really are,” “When I think about who we the ethnic Korean are, I am unsure that the ethnic Korean identity that I know is correct,” “When I think about who ethnic Koreans were in the past, I don't know what ethnic Koreans were really like,” “When I think about who ethnic Koreans are, the image of ethnic Korean people in my mind is unclear,” and “If I were asked to describe who ethnic Korean people are, my description might end up being ambiguous,” 1 not at all , 9 very much, α = 0.90.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because people define themselves as members of multiple social groups and categories, some with overlapping attributes (cf. Roccas & Brewer, 2002), the notion of identity-centrality may be better understood in terms of relative identity-centrality-people differentially weight the importance of groups and identities to their self-concept (Jung, Hogg, & Lewis, 2018). Research shows that relatively stronger subgroup (vs. superordinate) identification predicts less endorsement of superordinate values and greater endorsement of subgroup values (Wan, Chiu, Peng, & Tam, 2007).…”
Section: Identit Y-centr Alit Y In Subg Roup-superordinate G Roup Rmentioning
confidence: 99%
“…It has been found that decreased perceptions of entitativity can increase group members’ intention to leave their ingroup (Sani, ). Identity–uncertainty has also been found to lead to disidentification from the group (Jung, Hogg, & Choi, , ; Jung, Hogg, & Lewis, ). However, the causal path from reduced entitativity through identity–uncertainty to emigration intention has not been directly tested.…”
Section: Introductionmentioning
confidence: 99%